Students’ Strategies In Coping With Anxiety In Speaking English - Raihana Khairunisa Nurahman; Istiqlaliah Nurul Hidayat; Abdul Rosyid (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2023)
The present research aims to analyse Students' Strategies in Coping with Anxiety in Speaking English. The research question of this research is what are the students’ strategies in coping with anxiety in speaking English. The aim of this research is to investigate the kinds of students’ strategies in coping with anxiety in speaking English. In this research the writer used a qualitative method with a case study approach. The data was collected from the students of second semester English Education Study Program Faculty of Teacher Training and Education Pakuan University. The instrument used were observation, questionnaire and interview. The result shows that the students of the second semester English Education Study Program Faculty of Teacher Training and Education Pakuan University carried out the five strategies, namely preparation, relaxation, positive thinking, peer seeking and resignation. It is in line with a theory proposed by Kondo & Ling (2004). The students apply these strategies with various activities. By doing these strategies the students can reduce the anxiety they feel when speaking English, feel more prepared to speak English, and calmer when speaking English. In addition, they can be more confident in speaking English and their ability to speak English can increase. Therefore, it is very good for students to do these strategies.